A marxist reading of Fitzgerald’s Novel: The Great Gatsby and The Beautiful and Damned - Mostafa, Tasmia (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.